The Effect of Rising Gold Prices on Acehnese Society's Investment Practices From an Islamic Economic Standpoint - Wardani, Susi; Marlenny, Hemma (Universitas Syiah Kuala, 2025)
The purpose of this study is to investigate the impact of rising gold prices on the Acehnese community's investing behavior, as well as explore the issue from an Islamic economic perspective. Gold is a popular investment product in Aceh due to its perceived stability and conformity to Sharia rules. Changes in investing patterns, including increased interest and altering strategies, have been prompted by the notable increase in gold prices in recent years. This study used a qualitative-descriptive methodology by observing and interviewing local investors. The results showed that while rising gold prices motivate the community to make long-term investments more actively, they also cause speculative tendencies that might be contrary to the Islamic precept of prudence. According to Islamic economic theory, gold investments are acceptable provided they are made with the intention of protecting wealth (hifzh al-mal) and do not include any aspects of gambling (maysir), uncertainty (gharar), or usury (riba). Therefore, Islamic financial literacy is essential to ensure that the community invests wisely and in accordance with the principles of maqasid al-sharia.